ALCAPA Presents in an Adult with Exercise Intolerance but Preserved Cardiac Function. (5th September 2012) - Liu, Yan; Miller, Beth W.
Abstract : Anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA) is a rare congenital anomaly that usually manifests as severe left-sided heart failure and mitral valve insufficiency during the first one to two months of life. The majority of these cases die in infancy if not corrected early upon presentation. Adulthood presentation is rare and most of the untreated patients who reach adulthood present with left ventricular dysfunction, severe mitral regurgitation, and sometimes myocardial infarction. Here we report a case of a 20-year-old woman with a history of exercise intolerance since childhood that was misinterpreted as asthma until a 2D-Echo revealed ALCAPA with RCA collaterals to the left anterior descending artery, preserved LV ejection fraction, and absence of apparent mitral valve abnormality. One month after the ALCAPA diagnosis, she successfully underwent surgical reconstruction of left main and pulmonary artery without any major complications. She had normal left ventricular function without apparent ischemic cardiac symptoms eighteen months after procedure.